2013
DOI: 10.4319/lo.2013.58.3.0997
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Antarctic phytoplankton species to ocean acidification: Growth, carbon acquisition, and species interaction

Abstract: Despite the fact that ocean acidification is considered to be especially pronounced in the Southern Ocean, little is known about CO 2 -dependent physiological processes and the interactions of Antarctic phytoplankton key species. We therefore studied the effects of CO 2 partial pressure (P CO 2 ) (16.2, 39.5, and 101.3 Pa) on growth and photosynthetic carbon acquisition in the bloom-forming species Chaetoceros debilis, Pseudo-nitzschia subcurvata, Fragilariopsis kerguelensis, and Phaeocystis antarctica. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
121
3
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 106 publications
(144 citation statements)
references
References 47 publications
18
121
3
2
Order By: Relevance
“…Our results also agree well with previous laboratory experiments, which have shown that Antarctic Chaetoceros isolates show little to no stimulation by increasing pCO 2 levels (Boelen et al 2011;Trimborn et al 2013;Hoppe et al 2015). Nonetheless, this genus dominated OA treatments in several experiments with natural assemblages from the Southern Ocean, suggesting it to be a 'potential winner of OA' (Tortell et al 2008;Feng et al 2010;Boelen et al 2011;Trimborn et al 2013).…”
Section: Assemblages Did Not Respond To Ocean Acidificationsupporting
confidence: 82%
“…Our results also agree well with previous laboratory experiments, which have shown that Antarctic Chaetoceros isolates show little to no stimulation by increasing pCO 2 levels (Boelen et al 2011;Trimborn et al 2013;Hoppe et al 2015). Nonetheless, this genus dominated OA treatments in several experiments with natural assemblages from the Southern Ocean, suggesting it to be a 'potential winner of OA' (Tortell et al 2008;Feng et al 2010;Boelen et al 2011;Trimborn et al 2013).…”
Section: Assemblages Did Not Respond To Ocean Acidificationsupporting
confidence: 82%
“…Acclimation to increased CO 2 has been reported in a number of studies, resulting in shifts in carbon and energy utilisation (Sobrino et al, 2008;Hopkinson et al, 2010;Hennon et al, 2014;Trimborn et al, 2014;Zheng et al, 2015). Numerous photophysiological investigations on individual phytoplankton species also report species-specific tolerances to increased CO 2 (Gao et al, 2012a;Gao and Campbell, 2014;Trimborn et al, 2013Trimborn et al, , 2014, and a general trend toward smaller-celled communities with increased CO 2 has been reported in ocean acidification studies globally . Changes in community structure were observed with increasing CO 2 , with taxon-specific thresholds of CO 2 tolerance (Hancock et al, 2017).…”
Section: Ocean Acidification Effects On Phytoplankton Productivitymentioning
confidence: 94%
“…Increased CO 2 enhanced rates of primary productivity (Wu et al, 2010;Trimborn et al, 2013) and growth (Sobrino et al, 2008;Tew et al, 2014;Baragi et al, 2015;Chen et al, 2015;King et al, 2015) in some diatom species, while others were unaffected (Chen and Durbin, 1994;Sobrino et al, 2008;Berge et al, 2010;Trimborn et al, 2013;Chen et al, 2015;Hoppe et al, 2015;King et al, 2015;Bi et al, 2017). In contrast, CO 2 -related declines in primary productivity and growth rate have also been observed (Barcelos e Ramos et al, 2014;Hoppe et al, 2015;King et al, 2015;Shi et al, 2017), suggesting that responses to ocean acidification are largely species specific.…”
mentioning
confidence: 93%
“…However, growth and/or carbon fixation of other diatoms (C. brevis, C. debilis, Rhizosolenia cf. alata, P. subcurvata and P. alata) and P. antarctica remained unaffected by lowered pH (Riebesell et al, 1991;Boelen et al, 2007;Hoogstraten et al, 2012;Trimborn et al, 2013;Hoppe et al, 2015) suggesting that overall, the SO phytoplankton species investigated do not seem to benefit from lowered pH levels.…”
Section: Ocean Acidification -Ph and Comentioning
confidence: 95%
“…Natural phytoplankton communities of the SO (Weddell Sea, Drake Passage, Western Antarctic Peninsula, Amundsen and Ross Sea) were found to actively take up CO 2 and HCO 3 − (Cassar et al, 2004;Tortell et al, 2008aTortell et al, , 2008bTortell et al, , 2010Neven et al, 2011;Tortell et al, 2013;Kranz et al, 2015;Trimborn et al, 2015), thus indicating the presence of a CCM. Also, laboratory studies have demonstrated the operation of CCMs in various SO diatoms (Chaetoceros debilis, Fragilariopsis kerguelensis, F. cylindrus, Nitzschia frigida, Pseudo-nitzschia subcurvata) and a prymnesiophyte (Phaeocystis antarctica), although important differences between species were seen in the ratios of HCO 3 − and CO 2 uptake and external CA activity (Mitchell and Beardall, 1996;Trimborn et al, 2013;Kranz et al, 2015;Young et al, 2015).…”
Section: Ocean Acidification -Ph and Comentioning
confidence: 99%